Unequal Pay or Unequal Employment? What Drives the Skill-Composition of Labor Flows in Germany? - Melanie Arntz; Terry Gregory; Florian Lehmer (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2012)
This paper examines the determinants of gross labour flows in a context where modeling the migration decision as a wage-maximizing process may be inadequate due to regional wage rigidities that result from central wage bargaining. In such a context, the framework that has been developed by Borjas et al. (1992) on the selectivity of internal migrants with respect to skills has to be extended to allow migrants to move to regions that best reward their skills in terms of both wages and employment. The extended framework predicts skilled workers to be disproportionately attracted to regions with higher mean wages and employment rates as well as higher regional wage and employment inequalities. Estimates from a labour flow fixed effects model and a GMM estimator show that these predictions hold, but only the effects for mean employment rates and employment inequality are robust and significant. The paper may thus be able to explain why earlier attempts to explain skill selectivity in Europe within a pure wage-based approach failed to replicate the US results.
Keywords: R23; J31; J61; 330